AIP Conference Proceedings 2009
DOI: 10.1063/1.3251243
|View full text |Cite
|
Sign up to set email alerts
|

Contact Resistance Studies of Metal on HOPG and Graphene Stacks

Abstract: Contact resistance is one of the major factors limiting the performance of future nanoelectronic devices. Although there has been significant progress in graphene based devices since 2004 [1,11,13,19,20], there have been few studies of factors such as metal type, metal workfunction and number of layers in the graphene stack on metal/graphene contact resistance. In this work, contact resistance measurements of various metals (Cr, Ni, Pd, Pt) on Highly Oriented Pyrolytic Graphite (HOPG) and graphene (single laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The total resistance (R T ) obtained from the two-point I SD -V SD measurement is the sum of the resistance of the single G-NS (R G−NS ) and of the two contact resistances (R C ) at the GUITAR-Ti/Au interface on each end: R T = R G−NS + 2R C . Previous studies on the contact resistance of single-and multilayered graphene to Ti/Au metal contacts have reported contact resistances of <250 Ω for multilayered graphene (~50 layers) [51], and~165 Ω for single-layered graphene [52]. A comparison of the contact resistances for Ni contacts on graphene and highly ordered pyrolytic graphite (HOPG) has shown that the measurements are approximately two orders of magnitude higher for Ni contacts on graphene than on HOPG.…”
Section: Electrical Characteristicsmentioning
confidence: 99%
“…The total resistance (R T ) obtained from the two-point I SD -V SD measurement is the sum of the resistance of the single G-NS (R G−NS ) and of the two contact resistances (R C ) at the GUITAR-Ti/Au interface on each end: R T = R G−NS + 2R C . Previous studies on the contact resistance of single-and multilayered graphene to Ti/Au metal contacts have reported contact resistances of <250 Ω for multilayered graphene (~50 layers) [51], and~165 Ω for single-layered graphene [52]. A comparison of the contact resistances for Ni contacts on graphene and highly ordered pyrolytic graphite (HOPG) has shown that the measurements are approximately two orders of magnitude higher for Ni contacts on graphene than on HOPG.…”
Section: Electrical Characteristicsmentioning
confidence: 99%
“…The total resistance (RT) obtained from the two-point I SD – V SD measurement is the sum of the resistance of the single G-NS (RnormalGNS) and of the two contact resistances (RCfalse) at the GUITAR–Ti/Au interface on each end: RT=RnormalGNS+2RC. Previous studies on the contact resistance of single- and multilayered graphene to Ti/Au metal contacts have reported contact resistances of <250 Ω for multilayered graphene (~50 layers) [51], and ~165 Ω for single-layered graphene [52]. A comparison of the contact resistances for Ni contacts on graphene and highly ordered pyrolytic graphite (HOPG) has shown that the measurements are approximately two orders of magnitude higher for Ni contacts on graphene than on HOPG.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the contact resistances for Ni contacts on graphene and highly ordered pyrolytic graphite (HOPG) has shown that the measurements are approximately two orders of magnitude higher for Ni contacts on graphene than on HOPG. This greater contact resistance is attributed to the higher charge density in HOPG [51]. Additionally, Venugopal et al have shown that the contact resistance for metal contacts on multilayered graphene decreases as the number of graphene layers increases [51]; this is because increasing the number of graphene layers results in increased carrier concentration, until the structure approaches that of HOPG, i.e., becomes more metallic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S16 †). 54,55 Regarding pAuNP_PVA samples, two relevant differences with respect to pAuNP_Cys LT and pAuNP_Cys HT appear: (i) pAuNP_PVA LT cannot be operated as an electrode (viz. monotasking substrate) because of the insulating properties of PVA; (ii) pAuNP_PVA HT shows the lowest sheet resistance (i.e.…”
Section: Electrical Characterizationmentioning
confidence: 99%